RETRACTED: A Methylene Blue Assisted Electrochemical Sensor for Determination of Drug Resistance of Escherichia coli - Duan, Rongshuai; Fang, Xiao; Wang, Dongliang (Frontiers in Chemistry, 2021)
Due to the abuse of antibiotics in clinical, animal husbandry and aquaculture, drug-resistant pathogens are produced, which poses a great threat to human and public health. At present, a rapid and effective drug sensitivity test method is urgently needed to effectively control the spread of drug-resistant bacteria. Using methylene blue as redox probe, the electrochemical signals of methylene blue in drug-resistant Escherichia coli strains were analyzed by CV method. Graphene ink has been used for enhancing the electrochemical signal. Compared with the results of traditional drug sensitivity test, we proposed a rapid electrochemical drug sensitivity test method which can effectively identify the drug sensitivity of Escherichia coli. The sensitivity of four E. coli isolates to ciprofloxacin, gentamicin and ampicillin was tested by electrochemical drug sensitivity test. The respiratory activity value %RA was used as an indicator of bacterial resistance by electrochemical method.